Process variations in the production of gluconic acid and glucose oxidase by fermentation using Penicillium funiculosum 4072 - Consignado, Lenita J. (1995)
Ten-liter fermentation runs were conducted to investigate some production processes for gluconic acid and glucose oxidase by Penicillum funiclosum 4072. The results of the batch fermentation with recycling of mycelia show that we can re-use the mycelia. using 10% glucose in the medium, high enzyme activity coupled with high production of gluconic acid were obtained in every 24 hours. In the fed-batch addition of nutrients, two methods of nutrient feeding were investigated: semicontinuous addition of nutrients with glucose, and semocontinuous addition of glucose only. (other nutrients charged at the start of the process). The results show little difference in the rate of fermentation. Yield of about 90% was obtained for both methods after 36 hours. The peak of enzyme activity was observed after 18 hours at 686 units/L for the former and 663 units/L for the latter. Both processes were not optimized which account for low level of glucose oxidase activity. In the fermentation using various concentrations of glucose of up to 25%, the 20% concentration gavethe highest enzyme activity at 2282 units/L after 24 hours with maximum calcium gluconate yield of 88% obtained after 48 hours.
Computer print-out.
Thesis (M.S. Chemical Engineering)--University of the Philippines Diliman.
Keywords: Glucuronic acid -- Production control; Fermentation; Glucose; Penicillium